Investigation of Rheology Biocopolymer Based on Starch-poly(sodium acrylate-co-acrylamide) - Soleimani, Fatemeh; Azadi, Fatemeh; Sadeghi, Hossein; Shahsavari, Hadis; Soleimani, Arezou; Sadeghi, Fatemeh (Asian Journal of Chemistry, 2013)
In the present paper, attention is paid to investigates rheology of a superabsorbent hydrogel based on starch and polyacrylonitrile. The physical mixture of starch and polyacrylonitrile was hydrolyzed by NaOH solution to yield starch-poly(sodium acrylate-co-acrylamide) superabsorbent hydrogel. A proposed mechanism for hydrogel formation was suggested and the structure of the product was established using FTIR spectroscopy.